OsLDDT1, encoding a transmembrane structural DUF726 family protein, is essential for tapetum degradation and pollen formation in rice - Sun, Zhihao (Plant science : an international journal of experimental plant biology, 2023)
Copyright © 2023 Elsevier B.V. All rights reserved.